PENGENALAN CERITA RAKYAT “BATURRADEN” MENGGUNAKAN FLASH (Information Technology and Telematics, 2014)
Abstract – The countries of Indonesia have many culture and art. One of them is a form of the legend which is lifted from folklore as the nation's cultural wealth of heritage predecessors which is  contain with a good example, the value of education, moral values​​, ethical values​​, and there are many more positive things are very important implanted into the soul of the child since an early age. Flash is a software that is widely used with web designers that used to create animated objects or text are  very amazing to create an interactive web site, attractive and dynamic. Here, the researchers are trying to make an animation using flash folklore Baturaden Timeline techniques. with design drawings, dialogue, time, soud using Storyboard so his net plot can be developed, from the look of the image and background research using how to edit and crop images using Photoshop CS3. In dubbing the story the  characters using dubbing techniques that used jet-recorded audio. and the  result of the making of this animation is the animation folklore with the title Baturraden using flash animation with seven stories in the character played by six, with the  total duration is 10 minutes and completely with a sound perkarakter. Keywords: : Folklore Baturraden, Multimedia, Macromedia Flash 8. Abstrak, Indonesia merupakan negara yang memiliki beranekaragam budaya dan seni. Salah satunya berupa bentuk legenda yang diangkat dari cerita rakyat sebagai kekayaan budaya bangsa warisan para pendahulu yang di dalamnya terkandung suri teladan, nilai pendidikan, nilai moral, nilai etika, dan masih banyak lagi hal-hal positif yang amat penting ditanamkan ke dalam jiwa anak semenjak usia dini. Flash adalah software yang banyak dipakai oleh desainer web yang digunakan untuk membuat animasi objek atau text yang sangat menakjubkan untuk membuat suatu situs web yang interaktif, menarik dan dinamis. Disini peneliti mencoba membuat animasi cerita rakyat baturaden mengunakan flash dengan teknik Timeline. dengan merancang gambar, dialog, waktu, soud mengunakan Storyboard sehingga jalanya alur cerita dapat dikembangkan, dari tampilan gambar dan background peneliti menggunakan cara mengedit dan memotong gambar menggunakan Photoshop CS3. Dalam pengisian suara pada karakter cerita menggunakan teknik dubbing yang direkam menggunakan jet-audio. Hasil akhir dari pembuatan animasi  ini adalah  animasi cerita rakyat berjudul Baturraden menggunakan flash dengan tujuh cerita animasi yang di perankan oleh enam karakter tokoh, dengan total durasi 10 menit dan dilengkapi dengan suara  perkarakter. Kata Kunci: Cerita Rakyat Baturraden, Multimedia, Macromedia Flash 8.